HUBUNGAN ANTARA KADAR DEBU TOTAL DAN PERSONAL HYGIENE DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA PENGOLAHAN KAYU DI CV INDO JATI UTAMA SEMARANG - Lisa Okta Permatasari; Mursid Rahardjo; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The wood processing industry has the potential to cause air pollution in the workplace in the form of wood dust. The purpose of this study was to analyze the relationship between total dust content and personal hygiene with pulmonary function disorder in wood processing workers in CV Indo Jati Utama Semarang using cross sectional design. The population in this study is the air that exists in the work environment of the company along with 65 workers from five parts in the wood processing industry. The sample of this research is 5 point of air sample location with 38 respondents who have fulfilled the inclusion criteria. Of the 38 workers it was found that 9 workers had normal function (23.7%), 2 workers had severe restriction (5.3%), 10 workers had moderate restriction disorder (26.3%), 15 workers had mild restriction (39, 5%) and 2 workers had severe obstruction (5.3%). The result of the research with fisher exact test showed that there was correlation of total dust content (p = 0,040), respirable dust level (p = 0,036), and use of Personal Protective Equipment (PPE) (p = 0,021). Inhaled dust levels are risk factors for lung function impairment (RP = 2.714; RP> 1). The conclusion in this research is there is correlation of total dust content, respirable dust level, and usage of PPE in wood processing worker at CV Indo Jati Utama Semarang.